2017
DOI: 10.3748/wjg.v23.i18.3349
|View full text |Cite
|
Sign up to set email alerts
|

Chronological age when healthcare transition skills are mastered in adolescents/young adults with inflammatory bowel disease

Abstract: AIMTo describe the longitudinal course of acquisition of healthcare transition skills among adolescents and young adults with inflammatory bowel diseases.METHODSWe recruited adolescents and young adults (AYA) with inflammatory bowel diseases (IBD), from the pediatric IBD clinic at the University of North Carolina. Participants completed the TRxANSITION Scale™ at least once during the study period (2006-2015). We used the electronic medical record to extract participants’ clinical and demographic data. We used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 33 publications
5
31
0
Order By: Relevance
“…Parents who are overloaded may not be giving feedback to the child about the child's self‐management skills, leading the child to wrongly assume this means they are doing well and give themselves a higher self‐report of their own HCT readiness. Previous work on HCT readiness shows that youth tend to have a dip in their self‐reported HCT readiness in the late teens and early 20s, when they are presumably taking on more tasks themselves (Stollon et al, ), so this scenario is possible. In this case, the youth's lack of HCT readiness may be contributing to a parent's level of role overload, and encouraging greater levels of youth self‐management may help both parents and youth.…”
Section: Discussionmentioning
confidence: 97%
“…Parents who are overloaded may not be giving feedback to the child about the child's self‐management skills, leading the child to wrongly assume this means they are doing well and give themselves a higher self‐report of their own HCT readiness. Previous work on HCT readiness shows that youth tend to have a dip in their self‐reported HCT readiness in the late teens and early 20s, when they are presumably taking on more tasks themselves (Stollon et al, ), so this scenario is possible. In this case, the youth's lack of HCT readiness may be contributing to a parent's level of role overload, and encouraging greater levels of youth self‐management may help both parents and youth.…”
Section: Discussionmentioning
confidence: 97%
“…Generally, they remark that it is developmentally appropriate for adolescents to have this information so that they can better monitor their health, make better decisions regarding risky health behaviors (i.e., smoking), and begin to take a more active role in interactions with their healthcare providers and in assuming responsibility for their health. Consistent with these perspectives, research demonstrates that assuming responsibility for one's health is a series of skills typically learned over the course of adolescence through repeated interactions with the healthcare system under the guidance of parents (e.g., Burstrom et al 2016;Doshi et al 2014;Stollon et al 2017). Genetic counselors and other health care providers who follow patients with LFS over time can also support increased understanding and responsibility over time, and help facilitate the transition to adult care.…”
Section: Discussionmentioning
confidence: 93%
“…Several studies have reported a significant and positive relationship between age and skill acquisition [ 35 , 36 , 37 , 38 , 39 ] with age predicting mastery of skills over time [ 35 ]. Previous studies also found that few AYAs achieve mastery of health care transition skills by age 18, especially in the domains of ‘disease self-management’ and ‘understanding of health insurance’ [ 36 , 37 , 38 ] emphasising the need to acknowledge that health transition does not end with the event of transfer but extends into young adulthood and hence adult services.…”
Section: Outcome Indicators Of Transitionmentioning
confidence: 99%